Daya Hidup Spermatozoa Sapi Limousin yang Dipreservasi dengan Metode Water Jacket dan Free Water Jacket (SPERMATOZOA VIABILITY OF LIMOUSIN CATTLE PRESERVED WITH WATER JACKET AND FREE WATER JACKET METHOD) - ., Indriani; Susilawati, Trinil; Wahyuningsih, Sri (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
This study aimed to determine the effect of different methods of saving the storage by using a waterjacket and a free water jacket to quality semen Limousin cattle after being stored at a temperature of 5°C.Semen used the criteria motility e” + + collected two times a week. Semen evaluated macroscopically andmicroscopically and diluted in the ratio 1: 1 using the Cauda Epididymal Plasma (CEP-2) diluent added10% egg yolk. Stored in the refrigerator temperature 5°C and semen quality  was observed immediatelyafter dilution, 1 hour, 2 hours, 3 hours, 24 hours, 48 hours and 72 hours. The results showed that themethod of free storage waterjacket better in maintaining the percentage of motility, viability, abnormalityand plasma membrane intact spermatozoa
Keywords: spermatozoa, liquid semen, storage methods